2016
DOI: 10.1016/j.ijid.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnostics in dog-mediated rabies: an overview of performance and a proposed strategy for various settings

Abstract: The diagnosis of dog-mediated rabies in humans and animals has greatly benefited from technical advances in the laboratory setting. Approaches to diagnosis now include the detection of rabies virus (RABV), RABV RNA, or RABV antigens. These assays are important tools in the current efforts aimed at the global elimination of dog-mediated rabies. The assays available for use in laboratories are reviewed herein, as well as their strengths and weaknesses, which vary with the types of sample analyzed. Depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…It has been estimated that an average of 8,528 dog bites are reported annually in Lao PDR [8] underlining the importance of rabies surveillance and control. More recently, studies have identified the increasing importance of dog rabies in Lao PDR [4], Cambodia [9], and southern China [10], examining diagnostic issues, case numbers, epidemiology and genetic relatedness of contemporary regional strains.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that an average of 8,528 dog bites are reported annually in Lao PDR [8] underlining the importance of rabies surveillance and control. More recently, studies have identified the increasing importance of dog rabies in Lao PDR [4], Cambodia [9], and southern China [10], examining diagnostic issues, case numbers, epidemiology and genetic relatedness of contemporary regional strains.…”
Section: Introductionmentioning
confidence: 99%
“…Current rabies surveillance guidelines focus on use of validated laboratory diagnostic tests, which are highly sensitive and specific 11,12 and emphasize the need for notifiability 13 . The World Animal Health Organization (OIE) provisions set out general principles for adequate surveillance systems 14 , but specific recommendations for rabies are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the observation of clinical signs and symptoms is still used to diagnose rabies. In such settings, due to a variable clinical manifestations, laboratory assistance may be required [6,25,26]. The DFA test is the gold standard for rabies diagnosis; the method requires an expensive fluorescence microscope, which is often only available at the national level.…”
Section: Discussionmentioning
confidence: 99%